Antarmuka Empatik: Studi Eksperimental pada Sistem Chatbot yang Responsif terhadap Mood Pengguna (International Forum of Researchers and Lecturers, 2025)
In the digital era that increasingly emphasizes human-computer interaction, the existence of an interface system that is not only functional but also able to understand the emotional state of the user is becoming increasingly important. This study aims to explore the effectiveness of empathetic interfaces in chatbot systems designed to respond adaptively to user moods. Empathetic chatbots are defined as artificial intelligence-based conversational agents that are able to recognize and adjust their verbal responses to user emotional expressions through linguistic analysis and non-verbal data such as response time and word choice. This study uses an experimental approach involving 60 participants from among students who interact with two types of chatbots: standard chatbots (non-empathetic) and empathetic chatbots. The analysis methods used include measuring the level of user satisfaction, empathy perception, and emotional comfort through a Likert scale questionnaire and quantitative data processing using a paired T-test.